2015
DOI: 10.1002/pola.27661
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched polytriazine grafted reduced graphene oxide and its application

Abstract: In this article, cyanuric chloride (CC) and hexamethylenediamine (HMD) as raw material, the grafting of hyperbranched polytriazine onto reduced graphene oxide surface (HBP‐RGO) was achieved by the repeated nucleophilic substitution between chlorine groups of CC and amino groups of HMD, respectively. The Fourier transform infrared, X‐ray photoelectron spectroscopic, Raman, transmission electron microscopic, thermogravimetric, and atomic force microscopic analysis showed that HBP‐RGO had been successfully prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…For example, rubber/hindered phenol or hindered amine such as tetrakis[methylene-3-(3-5-di-tetra-butyl-4-hydroxy phenyl) propionyloxy]methane (AO-60) [11], triethylene glycolbis-[3-(3-tertbutyl-4-hydroxy-5-methyl phenyl)propionyloxy] (AO-70) [11], 3,9-bis[1,1-dimethyl-2-{b-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-eth yl]-2,4,8,10-tetraoxaspiro [5,5]-undecane (AO-80) [12], 2,20-methylene bis(6-tert-butyl-4-methylphenol) (AO-2246) [13], and N,N-dicyclohexyl-2-benzothia zolylsulfenamide (DZ) [14] have been widely investigated as a type of high performance damping material [15]. Moreover, in order to explore the damping mechanism in the hybrids, Zhao et al first investigate the damping mechanism of the nitrile-butadiene rubber (NBR)/AO-80 hybrids in a quantitative manner with the help of molecular dynamics (MD) simulation and attribute the cause of maximum dynamic property to the largest number of H-bonds and the greatest binding energy as well as the minimum fractional free volume (FFV) by a combination with the experimental results [16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, rubber/hindered phenol or hindered amine such as tetrakis[methylene-3-(3-5-di-tetra-butyl-4-hydroxy phenyl) propionyloxy]methane (AO-60) [11], triethylene glycolbis-[3-(3-tertbutyl-4-hydroxy-5-methyl phenyl)propionyloxy] (AO-70) [11], 3,9-bis[1,1-dimethyl-2-{b-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-eth yl]-2,4,8,10-tetraoxaspiro [5,5]-undecane (AO-80) [12], 2,20-methylene bis(6-tert-butyl-4-methylphenol) (AO-2246) [13], and N,N-dicyclohexyl-2-benzothia zolylsulfenamide (DZ) [14] have been widely investigated as a type of high performance damping material [15]. Moreover, in order to explore the damping mechanism in the hybrids, Zhao et al first investigate the damping mechanism of the nitrile-butadiene rubber (NBR)/AO-80 hybrids in a quantitative manner with the help of molecular dynamics (MD) simulation and attribute the cause of maximum dynamic property to the largest number of H-bonds and the greatest binding energy as well as the minimum fractional free volume (FFV) by a combination with the experimental results [16].…”
Section: Introductionmentioning
confidence: 99%
“…This method is based on the design concept of organic hybrid damping materials . Liu et al . found that the addition of hindered phenolic antioxidants improves the damping properties of XNBR remarkably.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported in our recent publications that functionalization of GO to generate derivatives could improve their dispersion and compatibility properties in the resin matrix [15,16,17]. Covalent functionalization of the GO surface is the most valid way to modulate thee chemical/physical features of GO sheets and provide suitable compatibility and dispersion, as well as accelerate the interfacial load transfer from the matrix to the sheet and improve the performances of the GO/polymer composite [18]. For instance, Liu [19] prepared a covalently bonded epoxy monomers (DER332) and curing agents (diamino diphenyl methane (DDM)-grafted GO (DED-GO) hybrid material through a three-step grafting procedure and acquired a higher improvement in tensile strength (30.0% at 0.2 wt% GO-DED) and elongation at break (16.0%) of the epoxy nanocomposite compared with the neat epoxy resin, respectively.…”
Section: Introductionmentioning
confidence: 99%